Extraction of Cellulose from Stem and Bark of Daphne papyracea and Grewia optiva Plants and Its Characterization - Rajaure, Anil; Chaudhary, Pratibha; Gharti, Susmita; Sigdel, Anil; Pathak, Ishwor; Prasad, Manoj Kumar; Oli, Hari Bhakta; Bhattarai, Deval Prasad (Amrit Research Journal, 2023)
Cellulose, the most abundant biopolymer on the earth, has been successfully extracted from bark and stem of Daphne papyracea and Grewia optiva plants. Extraction of cellulose was performed by a series of sequences; pre-alkalization, alkalization, acetylation and acid hydrolysis processes. The extracted cellulose was dried and weighed. The yield % of the cellulose in the bark and stem of Daphne papyracea was found to be 28.43 % and 38.63%, respectively, and in the bark and stem of Grewia optiva was found to be 27.2% and 35.23%, respectively. Extracted cellulose was further characterized by FESEM, XRD and FTIR measurement method. The cellulose content in the stem of the plant is found higher than that of bark. From quantitative point of view, it is recommended as a raw material for paper making industries.